Adaptation of the digital addiction scale for children into Turkish: reliability and validity analysis - Kaçmaz, Cihangir; Cumurcu, Hatice Birgül; Çelik, Osman Tayyar (Journal of Dependence, 2023)
Objective: The aim of this study is to adapt the Digital Addiction Scale for Children into Turkish and to conduct a reliability and validity study with psychometric analyses. Method: The study was conducted with 326 secondary school students, 165 girls and 161 boys, using convenience sampling method. After the language validity study, the structure of the scale was examined with confirmatory factor analysis, and similar scale validity and item discrimination power were tested. In addition, Cronbach Alpha reliability coefficient was calculated. Results: As a result of the analyses, the two-factor structure of the scale was confirmed as interpersonal relationships and introverted factors. It was determined that the item discrimination power and item-total test correlations were high for the lower and upper 27% groups, and the correlation with the scores of the "Digital Game Addiction" scale applied within the scope of similar scale validity was high. Finally, Cronbach Alpha reliability coefficient was calculated as ,84 for interpersonal relationships, ,85 for introverted factors and ,90 for the overall scale. Conclusion: Digital Addiction Scale for Children is a valid and reliable scale to measure the digital addictions of secondary school students in Turkey.